2014
DOI: 10.1093/pcp/pct182
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2B Monoubiquitination is Involved in the Regulation of Cutin and Wax Composition in Arabidopsis thaliana

Abstract: The plant cuticle is a chemically heterogeneous lipophilic layer composed of a cutin polymer matrix and waxes which covers the aerial parts of plants. This layer plays an essential role in the survival of plants by protecting them from desiccation and (a)biotic stresses. Knowledge on the gene networks and mechanisms regulating the synthesis of cuticle components during organ expansion or stress response remains limited however. Here, using five loss-of-function mutants for histone monoubiquitination, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…Precise role of H2Bub1 in plant defense against pathogens still remains largely unclear. Structure defects, e.g., thinner cell walls and altered surface cutin and wax compositions, together with impaired induction of some defense genes might have partly contributed to the increased susceptibility to pathogen infection in the hub mutant plants (Dhawan et al, 2009; Ménard et al, 2014). It is worthy noting that the sdg8 mutants impaired in H3K36me3 deposition also display reduced resistance to necrotrophic fungal pathogen infection (Berr et al, 2010, 2012; Palma et al, 2010).…”
Section: H2b Monoubiquitination In Arabidopsismentioning
confidence: 99%
“…Precise role of H2Bub1 in plant defense against pathogens still remains largely unclear. Structure defects, e.g., thinner cell walls and altered surface cutin and wax compositions, together with impaired induction of some defense genes might have partly contributed to the increased susceptibility to pathogen infection in the hub mutant plants (Dhawan et al, 2009; Ménard et al, 2014). It is worthy noting that the sdg8 mutants impaired in H3K36me3 deposition also display reduced resistance to necrotrophic fungal pathogen infection (Berr et al, 2010, 2012; Palma et al, 2010).…”
Section: H2b Monoubiquitination In Arabidopsismentioning
confidence: 99%
“…In Arabidopsis , HISTONE MONOUBIQUITINATION1 (HUB1) and HUB2 act nonredundantly but possibly as a hetero‐tetramer E3, whereas UBIQUITIN CONJUGATING ENZYMES1 (UBC1) and UBC2, but not UBC3, act redundantly as E2 in H2B monoubiquitination (Fleury et al ., ; Liu et al ., ; Cao et al ., ; Xu et al ., ). Characterization of the hub1 , hub2 , hub1hub2 and ubc1ubc2 mutants has revealed that H2Bub1 regulates multiple processes, including cell cycle and plant growth (Fleury et al ., ; Lolas et al ., ), seed dormancy (Liu et al ., ), leaf cuticle formation (Ménard et al ., ), flowering (Cao et al ., ; Gu et al ., ; Xu et al ., ), circadian clock and photomorphogenesis (Bourbousse et al ., ; Himanen et al ., ), as well as plant defense (Dhawan et al ., ; Zou et al ., ). More recent studies have demonstrated that knockdown of HUB1/HUB2 in tomato also affects plant response to pathogens (Zhang et al ., ) and loss of HUB1/HUB2 in rice leads to early heading, dwarfism and anther developmental defects (Cao et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Highlights of the advances in this area comprise the identification of an ABC transporter ABCG32/PEC1 involved in cuticle assembly (Bessire et al, 2011), the description of several classes of transcription factors involved in cutin and wax biosynthesis (Javelle et al, 2010; Seo et al, 2011; Nadakuduti et al, 2012) or post-transcriptional regulation of cuticle biosynthesis by the zinc-finger protein SERRATE (Voisin et al, 2009). The involvement of protein monoubiquitination in the regulation of cuticle biosynthesis was recently documented as several genes of cutin and wax biosynthetic pathway were found to be targets for histone H2B monoubiquitination (Ménard et al, 2014). …”
Section: Introductionmentioning
confidence: 99%